2022
DOI: 10.53730/ijhs.v6ns5.10364
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hypothyroidism in infertile women and its correlation with the pituitary gland hormones

Abstract: Infertility is defined as a condition in which a woman cannot conceive after 12 months of a normal sexual relationship without the use of contraception. The study aimed to evaluate hypothyroidism prevalence, thyroid and pituitary gland hormones assessment in infertile women's serum, and their correlation in Basra, Iraq. The research was conducted at Ibn-Gzouan Hospital for Obstetrics and Gynecology in Basra, southern Iraq, between October 2021 and March 2022. In our research, 28 infertile women with hypothyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Include India, Nigeria, democratic republic of Congo, Pakistan and china. 1 Other studies revealed that malaria and acute respiratory infection are higher among children in rural setting and children whose mothers are 16-17 and 28-33 years of age, most of these studies considered childhood morbidity at country level. 2 Morbidity condition are more prevalent in the children who are exposed to various risk factors like overcrowding, poor nutrition etc.…”
Section: Introductionmentioning
confidence: 99%
“…Include India, Nigeria, democratic republic of Congo, Pakistan and china. 1 Other studies revealed that malaria and acute respiratory infection are higher among children in rural setting and children whose mothers are 16-17 and 28-33 years of age, most of these studies considered childhood morbidity at country level. 2 Morbidity condition are more prevalent in the children who are exposed to various risk factors like overcrowding, poor nutrition etc.…”
Section: Introductionmentioning
confidence: 99%